ENERAPAN METODE FORWARD CHAINING DALAM SISTEM PAKAR DIAGNOSA KERUSAKAN AIR CONDITIONER (AC) BERBASIS WEB - Muhammad Rizal Dwiki; Ahmad Heru Mujianto; Mashuri, Chamdan; Sri Widoyoningrum (Fakultas Teknologi Informasi, 2024)
Air conditioners (ACs) are widely used cooling devices in various places such as homes, offices, ANDeducational institutions. Continuous use of ACs often leads to malfunctions that require hANDling bytechnicians. However, newly graduated technicians often struggle to diagnose malfunctions efficiently due toa lack of experience. To address this issue, this research aims to develop a web-based expert system using theforward chaining method, designed to assist AC technicians in diagnosing malfunctions quickly ANDaccurately. The forward chaining method is employed to trace symptoms through a series of questions thathelp technicians identIFy the parts that need repair, covering 30 symptoms AND 13 AC malfunctions. Thisexpert system is expected to improve the efficiency of technicians in diagnosing AND repairing ACs. Theresults of the research indicate that the developed expert system functions well, facilitates technician accessfrom anywhere with a user-friendly interfaceKeywords: Air conditioner, expert system, forward chaining, malfunction diagnosis, web-based.